From solid solutions to fully phase separated interpenetrating networks in sputter deposited "immiscible" W–Cu thin films. (15th October 2015) - Vüllers, F.T.N.; Spolenak, R.
Graphical abstract: Abstract: W–Cu alloys are typically used for heat sinks, radiation shielding or high performance contact materials. Their immiscibility leads to interpenetrating structures, with typically smallest microstructural length scales on the order of several micrometres. This work focusses on tuning this length scale from the atomic level to the nanometre and submicron range. This is made possible by exploiting the two constituents' immiscibility in thermodynamic equilibrium as well as the lack of Cu segregation to W grain-boundaries, thus allowing for the growth of the two phases. The system is studied in the complete concentration range and microstructure is related to both mechanical and electronic properties.